O08.1 Understanding the experiences of ymsw in accessing health servies, sti, hiv and other realted services in lahore, pakistan. (8th July 2017) - Osama, Muhammad
Abstract : Introduction: In Pakistan, Young males sex workers (YMSW) community is socially excluded from the main stream society which makes them vulnerable towards HIV and STI. YMSW seldom access health care services due to stigma and discrimination by health care providers. Methods: Naz Male Health Alliance (NMHA) is the first ever non-governmental technical support agency in Pakistan that exists to improve sexual health, welfare and human rights for MSM, TG, sexual minorities and their partners. FGD was conducted in Lahore city with 11 YMSW between the age of 18 to 24, sample was gathered by using cross sectional technique with the support of peer lead approach. Results: 55% respondent reported the extreme level of sexual abuse and 50% reported they were raped by their doctor. 70% reported to bring their family that leads to breach of confidentiality however 80% agreed that YMSW would be sent back to bring their parents for STI treatment. 70% reported, it was harder to negotiate condom with client. None of the participants knew of any Young PLHIV MSW however the participants were of the view that medical staff would ask the young PLHIV to bring his family along with. Effects of breach of confidentiality about sexuality have very negative consequences because some reported, cases of suicide as a result of inappropriate disclosure made to family. Conclusions: NMHA established a drop-in-centre in Lahore where MSM/MSW of any age can get services of STI treatment, VCCT, Psychosocial counselling and condoms/lubricants free of cost and without any stigma, discrimination. Although there is a need to establish more drop in centres to cover more geographical area also public and private sector partnership would enhance the services in more effective way.